Sexual violence and rape among young migrants in Sweden: a cross-sectional study on prevalence, determinants, perpetrators, and reporting patterns - Baroudi, Mazen; Nkulu Kalengayi, Faustine Kyungu (Frontiers in Public Health, 2024)
BackgroundYoung migrants are particularly vulnerable to SV (SV) due to their age and the challenges of migration. However, there is limited knowledge regarding SV among young migrants in Sweden. This study aims to assess the prevalence, determinants, perpetrators, and reporting patterns of SV and rape.MethodsWe analyzed data from the 2018 survey on migrants’ sexual and reproductive health and rights, involving 1773 migrants aged 16–29. We estimated prevalence rates and calculated crude and adjusted prevalence ratios (APR) with 95% confidence intervals (CI) using descriptive and log-binomial regression analyses.ResultsThe overall prevalence of SV was 25.1%, with rape at 9%. Higher SV prevalence were reported by non-binary individuals (APR: 2.60, CI: 1.54 to 4.38), Lesbian, Gay, Bisexual and Asexual (LGBA) individuals (APR: 1.56, CI: 1.22 to 2.01), those with 10–12 years (APR: 1.35, CI: 1.04 to 1.74) and over 12 years of education (APR: 1.61, CI: 1.23 to 2.11), and migrants awaiting asylum decisions (APR: 1.67, CI: 1.25 to 2.23). Rape prevalence was higher among those born in non-conflict settings (APR: 2.38, CI: 1.43 to 3.97), non-binary individuals (APR: 3.32, CI: 1.35 to 8.18), and LGBA individuals (APR: 1.68, CI: 1.02 to 2.75). Although men reported higher SV and rape levels than women in descriptive and bivariate analyses, these differences were not significant in multivariate analyses. Perpetrators included strangers (46.3%), partners (24.8%), family/friends (15.8%), and colleagues (15.4%). Most survivors did not report SV (63.7%) but confided in friends/relatives (29%) and trusted individuals like teachers/counselors (9.5%), with fewer reporting to authorities (3.4%).ConclusionThe findings urge policymakers to prioritize targeted interventions, raise awareness, provide comprehensive support services tailored to the diverse needs of migrant groups, various perpetrator types, and the individual, systemic, and structural factors influencing reporting behaviors. These initiatives should adopt a migration-trajectory approach that recognize that migrants may have experienced SV throughout their journey and consider the unique experiences and vulnerabilities of non-binary individuals, LGBA individuals, those with low education levels, and migrants without formal residence status, regardless of their origin.